Application of Rasch Analysis to Measure the Validity and Reliability of the Academic Resilience Student Scale - Suciani Latif; Akhmad Harum; M. Fiqri Syahril (Universitas PGRI SUMATERA BARAT, 2024)
Student academic resilience refers to a person's ability to overcome challenges and difficulties in a higher education context, which includes the ability to remain resilient and productive amid academic pressures, challenging tasks, and changing educational environments. The purpose of the study was to evaluate the validity and reliability of the student academic endurance scale through the Rasch analysis approach. The results showed the unidimensionality analysis in raw variance explained by means and unexplained variance in the first contrast. The results of the unidimensionality analysis of the academic resilience scale were obtained: raw variance explained by measures with a value of 36% and unexplained variance in 1st of 8.1%. The score shows that raw variance explained by measures (36%) is greater than 20% and unexplained variance in 1st (8.1%) is below 15%. In the analysis results, 3 items do not match (misfits). The processing of the mean value (1.01) is added to the standard deviation (0.22), which is 1.23. Items that have a logit value greater than 1.23 are item numbers 9, 13, and 14. The acquisition of a larger logit value can be interpreted if items numbers 9, 13, and 14 are too difficult for respondents to answer. Three items on the academic resilience scale indicate if an item does not match. This can be interpreted as an academic resilience scale measuring tool that is appropriate for measuring student academic resilience.